Integrasi Nilai Pendidikan Islam dengan Budaya Jawa dalam Perspektif Emha Ainun Nadjib - Ahmad Solihin; Muhammad Azmi Al-Farisi (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2025)
This study explores the idea of ​​integration between Islamic educational values ​​and Javanese culture according to Emha Ainun Nadjib through an analysis of his works. This study includes a library research study using a qualitative descriptive method with a character approach. Data sources were obtained from: interviews with figures (Cak Nun) and his biological child (Sabrang MDP), as well as an inventory of his thoughts in the form of books, the CakNun.com YouTube channel which is directly managed by Rumah Maiyah and Kiai Kanjeng. The results of the study show that Javanese cultural values ​​and educational values ​​according to Cak Nun Islam's view are almost incompatible with each other. The verse of the Qur'an which reads "famayyakmal mitsqola dzarrotin khoiroyyaroh wa mayyakmal mitsqola dzarrotin syarroiyaroh", in Javanese society before the arrival of Islam there was a philosophy of "ngunduh woing pakarti". Javanese people already have knowledge based on the results of their ijtihad, so that Javanese people understand what is good and bad in their lives. Keywords : Integration, Value of Islamic education, Javanese Culture, Emha Ainun Nadjib